2011
DOI: 10.1111/j.1365-2958.2011.07703.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Trypanosoma brucei RAD51 paralogues in DNA repair and antigenic variation

Abstract: Homologous recombination in Trypanosoma brucei is used for moving variant surface glycoprotein (VSG) genes into expression sites during immune evasion by antigenic variation. A major route for such VSG switching is gene conversion reactions in which RAD51, a universally conserved recombinase, catalyses homology-directed strand exchange. In any eukaryote, RAD51-directed strand exchange in vivo is mediated by further factors, including RAD51-related proteins termed Rad51 paralogues. These appear to be ubiquitous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 141 publications
(241 reference statements)
2
39
0
Order By: Relevance
“…Sequence alignments reveal that the parasite RAD51 homologs share between 60 to 80% sequence identity with human RAD51 and that sequence conservation appears to extend outside the RecA fold, as an HhH and a PM motif have been reported in TbRad51 (179)(180)(181). Genetic analysis in T. brucei revealed that Rad51 Ϫ/Ϫ mutants display increased sensitivity to DNA-damaging agents, such as methyl methanesulfonate (MMS) and phleomycin, and reduced integration of transformed DNA, supporting a role in homologous recombination (113,179,182). In vivo, RAD51 is known to assemble at DSB sites, where it forms discrete nuclear foci after DNA damage (183,184).…”
Section: Homologous Recombinationmentioning
confidence: 90%
“…Sequence alignments reveal that the parasite RAD51 homologs share between 60 to 80% sequence identity with human RAD51 and that sequence conservation appears to extend outside the RecA fold, as an HhH and a PM motif have been reported in TbRad51 (179)(180)(181). Genetic analysis in T. brucei revealed that Rad51 Ϫ/Ϫ mutants display increased sensitivity to DNA-damaging agents, such as methyl methanesulfonate (MMS) and phleomycin, and reduced integration of transformed DNA, supporting a role in homologous recombination (113,179,182). In vivo, RAD51 is known to assemble at DSB sites, where it forms discrete nuclear foci after DNA damage (183,184).…”
Section: Homologous Recombinationmentioning
confidence: 90%
“…Indeed, though this switch reaction does not involve DNA rearrangements, it remains possible that it shares repair-related or replication-related functions that act in recombination-based switching (see below). Such a link would explain why mutation of core homologous recombination (HR) factors not only impairs VSG switching by recombination (see below), but also VSG switching by transcription (108)(109)(110), and why multiple treatments that cause DNA damage or replication arrest in T. brucei can elevate silent BES expression (111).…”
Section: The Genomic Components Of Antigenic Variation In Trypanosomamentioning
confidence: 99%
“…5) have been limited to understanding the activation of intact VSGs (106,108,110,114,117,(127)(128)(129). This stems from the fact that these studies have used in vivo or in vitro selection strategies that detect the most frequently activated VSGs; the lack of detectable mosaic VSG formation in these studies may suggest that SGC is less efficient than intact VSG conversion, though a mechanistic switch during an infection cannot be currently ruled out.…”
Section: Activation Of Intact Vsgs Involves Homologous Recombinationmentioning
confidence: 99%
See 2 more Smart Citations